Simultaneous CMOS-Based Imaging of Calcium Signaling of the Central Amygdala and the Dorsal Raphe Nucleus During Nociception in Freely Moving Mice - Rebusi, Romeo; Olorocisimo, Joshua Philippe; Briones, Jeric; Ohta, Yasumi; Haruta, Makito; Takehara, Hironari; Tashiro, Hiroyuki; Sasagawa, Kiyotaka; Ohta, Jun (Frontiers in Neuroscience, 2021)
Fluorescence imaging devices have been indispensable in elucidating the workings of the brain in living animals, including unrestrained, active ones. Various devices are available, each with their own advantages and limitations in terms of many factors. We have developed CMOS-based needle-type imaging devices that are small and lightweight enough to be doubly-implanted in freely-moving mice. The design also allowed angled implantations to avoid critical areas. We demonstrated the utility of the devices by using them on GCaMP6 mice in a formalin test experiment. Simultaneous implantations to the capsular-lateral central amygdala (CeLC) and dorsal raphe nucleus (DRN) were proven to be safe and did not hinder the execution of the study. Analysis of the collected calcium signaling data, supported by behavior data, showed increased activity in both regions as a result of pain stimulation. Thus, we have successfully demonstrated the various advantages of the device in its application in the pain experiment.